Equipement culturel et développement urbain : le centre d’art contemporain WIELS, héraut des logiques de transformation d’un quartier populaire ? - Simon Debersaques (Brussels Studies)
The opening in 2007 of the first contemporary art centre in Brussels in the lower part of the municipality of Forest, which is characterised by an industrial urban fabric and socioeconomic insecurity, seems to have marked a new era for this neighbourhood. WIELS defines itself as "an international laboratory for the creation and diffusion of contemporary art". Using a typology based on international literature, the objective of the study is to confront the rationale behind the creation of this cultural institution with the social and spatial transformations which have taken place in the neighbourhood since its establishment. In this article, we attempt to understand how WIELS contributes to urban development through culture. By combining different qualitative methods, it is clear that although WIELS was initially caught in a conflict between property income and openness towards its neighbourhood, certain tangible and discursive elements might prompt us to consider WIELS as one of the components in the formation of a new creative metropolitan centrality.